A case of sigmoid colon perforation due to segmental absence of intestinal musculature (SAIM) accompanied by vascular Ehlers–Danlos syndrome: a case report - Kosuke Funaki; Tomonori Akagi; Hidefumi Shiroshita; Yusuke Itai; Kiminori Watanabe; Takashi Shuto; Yoshitake Ueda; Tsuyoshi Etoh; Shinji Miyamoto; Tsutomu Daa; Masafumi Inomata (Surgical Case Reports, 2023)
Abstract Background Segmental absence of intestinal musculature (SAIM) is a partial defect of the intrinsic muscular layer of the intestinal tract. In this report, we describe a case of perforation of the sigmoid colon due to SAIM accompanied by vascular Ehlers–Danlos syndrome (vEDS), which was successfully treated by surgical therapy. Case presentation A male in his 30 s was being followed up for vEDS diagnosed by genetic testing. He had undergone two major vascular surgeries, abdominal aortic artery revascularization and thoracic endovascular aortic repair for a residual dissection and enlarging abdominal aortic aneurysm. On postoperative day 11, the patient developed perforation of the sigmoid colon for which intraperitoneal lavage and drainage, Hartmann surgery, and transverse colostomy were performed. Histological findings showed no disturbance of blood flow or diverticulum but did show a defect in the intrinsic muscular layer around the perforation site, leading to the pathological diagnosis of SAIM and associated perforation of the sigmoid colon. Postoperatively, the patient had no complications and was discharged on postoperative day 18. The patient is being followed as an outpatient and has experienced no relapse. Conclusions Both SAIM and vEDS, which may be related diseases, are associated with the presence of tissue fragility and have a high potential to cause intestinal perforation Caution should be exercised during surveillance in patients with constipation and examinations that cause increased intestinal pressure.